Awareness, Drivers, Actions, and Barriers of Sustainable Construction in Kuwait. (2015) - AlSanad, Shaikha
Abstract: The construction industry has a significant impact on the environment. It is responsible for a large proportion of global CO2 emissions, as well as the use of both natural resources and energy reserves. Green building (GB) practices are becoming increasingly recognized as a way of mitigating CO2 emissions and energy consumption, with environmental, economic, financial, social and benefits accruing. This paper reports the results of a study about the opportunities to promote sustainable construction (SC) practices in Kuwait. This entails identifying the current status of SC practices, the awareness level and knowledge of construction stakeholders, the key drivers that motivate the implementation of green practices, as well as barriers to SC. After comprehensive reviewing the literature, the data is conducted and collected through quantitative approach by questionnaires survey. The judgmental and snowball sampling techniques are used for the data collection. The local stakeholders associated with the Kuwait construction industry were the target population and used as a platform to obtain the data. A total of 678 questionnaires were distributed and 504 completed questionnaires were received. The quantitative data is then analyzed through descriptive analysis and inferential statistics. The main findings of this research are as follows: implementation of the concept of SC is low in the Kuwaiti construction industry; more action and strategies to improve and encourage this concept are therefore required in order for it to be applied efficiently in future projects; lack of awareness was found to be the main barrier to the use of SC approaches in Kuwait; the Kuwaiti government must take initiatives in terms of introducing standards, policies and incentives to promote SC. The findings of this study provide valuable information for organizations that intend to participate in green construction projects in Kuwait.